A comparative study of time-based maintenance and condition-based maintenance for optimal choice of maintenance policy. Issue 12 (1st December 2016) - Kim, Jeongyun; Ahn, Yongjun; Yeo, Hwasoo
Abstract: Cost-effective maintenance of infrastructure systems within an acceptable level of safety and performance is the major concern of managing agencies. Recent maintenance approaches have offered two distinct maintenance policies: time-based maintenance (TBM) and condition-based maintenance (CBM). This paper compares the two policies under different cost environments for stochastically deteriorating infrastructures. The performance of TBM and CBM is evaluated from the viewpoint of condition transition and life cycle cost. We found the optimal maintenance solutions for TBM and CBM using dynamic programming and performed a simulation study. The simulation study showed that TBM causes some unexpected deterioration that leads to high cost, while CBM maintains a certain level of condition steadily under consistent inspection, which enables steady spending at the management level. The life cycle cost under CBM is relatively symmetric and has a more concentrated distribution than TBM, which has a large number of outliers from unexpected deteriorations. Finally, we evaluated the life cycle cost with a change in the inspection–repair cost ratio to find the most appropriate cost environment for each maintenance policy. While CBM needs periodic inspections, it still has more advantages than TBM when the inspection cost is relatively low.